1992
DOI: 10.1117/12.138852
|View full text |Cite
|
Sign up to set email alerts
|

<title>Recent advances in ocean-surface characterization by a scanning-laser slope gauge</title>

Abstract: In this paper, we describe TRW's latest version of the scanning laser slope gauge (SLSG) which was used to characterize the sea surface in a recent ocean experiment. The SLSG, capable of measuring the spatial distribution and temporal evolution of the surface slopes of a patch of ocean, provides ground truth data which form a quantitative basis for the understanding of ocean wind-wave interactions and the development and validation of radar scattering models relevant to ocean remote sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…To overcome these problems, spatial measurements of capillary-gravity waves have been recently attempted. Banner et al [1989] used stereophotogrammetry from an offshore rese.•ch platform to obtain wavenumber spectra for waves between 0.2 and 1.6 m. For shorter waves, a scanning laser slope gauge (SLSG) has been used by Barter et al [1990], Lee et al [1992], and Li et al [1993]. Jiihne and Riemer [1990] have conducted extensive measurements of wavenumber spectra in the capillarygravity range using a digital image processing technique at a large wind-wave flume.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, spatial measurements of capillary-gravity waves have been recently attempted. Banner et al [1989] used stereophotogrammetry from an offshore rese.•ch platform to obtain wavenumber spectra for waves between 0.2 and 1.6 m. For shorter waves, a scanning laser slope gauge (SLSG) has been used by Barter et al [1990], Lee et al [1992], and Li et al [1993]. Jiihne and Riemer [1990] have conducted extensive measurements of wavenumber spectra in the capillarygravity range using a digital image processing technique at a large wind-wave flume.…”
Section: Introductionmentioning
confidence: 99%
“…The long wave breaking significantly increases the probability of very large slopes beyond six times of the standard deviation. This has been observed by Lee et al (1995Lee et al ( , 1996 from the grazing-angle-dependent signals and their Doppler spectra. The long wave breaking and cresting give strongly reflecting facets at angles well beyond those predicated in simple specular-point theory, including out to grazing angles.…”
Section: F Non-gaussian Pdf Of Slopesmentioning
confidence: 72%
“…The long wave breaking and cresting give strongly reflecting facets at angles well beyond those predicated in simple specular-point theory, including out to grazing angles. Lee et al (1995) found strong evidence that in low grazing angles, lifetimedominated, non-Bragg scattering contributes noticeably to returns for both polarizations, but is dominant in providing return for the horizontal polarization. Without consideration of long wave breaking, our model on the PDF of slopes cannot accurately predict the returns of both polarizations at low grazing angles, especially for the horizontal polarization.…”
Section: F Non-gaussian Pdf Of Slopesmentioning
confidence: 97%
See 1 more Smart Citation
“…(2) Field data obtained by Valenzuela (1978) using a four-frequency radar show that the spectrum between wavelengths of 72 cm and 2 cm under U10 = 2.5 ms -1 has a slope steeper than co 5 More spectra with steeper slopes than m 5 in the ocean were also observed by Palm et al (1976), Tang and Shemdin (1983) and Lee et al (1992) by using a laser-optical sensor.…”
Section: Introductionmentioning
confidence: 81%